Plane geometry drawing tutorial (2014)
A tutorial has been developed with the aim of making geometry drawing teaching easier. It arises as a helpful tool for lecturers and engineering undergraduate students, with the objective of giving support to theoretical and practical lessons in plane geometry drawing. This easy-to-use tutorial provides users with interactivity, practical videos, self-evaluation, fundamental lessons, and “step by step” teaching due to the different levels of conceptual complexity included in its contents.